Transcriptome changes and deregulated biological pathways associated with NF1-mutated pheochromocytoma - Snezhkina, Anastasiya; Kobelyatskaya, Anastasiya; Fedorova, Maria; Kalinin, Dmitry; Pavlov, Vladislav; Kudryavtseva, Anna (Archive of Oncology, 2025)
Background: Pheochromocytoma (PHEO) is a rare tumor of intraadrenal sympathetic origin. At least of 25-30% of PHEOs have been found to be linked to germline or somatic mutations in the NF1 gene, which functions as a tumor suppressor. Despite the high frequency of NF1 mutations in PHEOs, the exact mechanism underlying the pathogenesis of these tumors has not yet been fully elucidated. Methods: A large-scale analysis of transcriptomic profiles and biological pathways associated with NF1-related PHEOs was conducted utilizing RNA-Seq and miRNA-Seq data from the The Cancer Genome Atlas (TCGA) project. Results: A total of 21 differentially expressed transcripts (14 genes, 3 long noncoding RNAs, and one microRNA) were identified in association with germline and somatic mutations in the NF1 gene. The present study detected a decrease in the mRNA levels of NF1, as well as of its interacting partners, SPRED3 and EZR. Decreased expression of oncogenic microRNA miR-423-3p was also observed. Seven differentially expressed genes (SHC3, SHC1, STAT3, NF1, KSR1, NOS2, and ALDOC) were found to be overrepresented in a number of distinct biological pathways, including those associated with RAS and HIF-1 signaling, pathway linked to resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors, and the growth hormone-associated pathway. These findings suggest deregulation of these pathways in NF1-mutated PHEOs. Conclusion: The results obtained demonstrate the consequences of NF1 mutations at the level of the transcriptome. Furthermore, they confirm a change in RAS signaling pathways in NF1-related PHEOs.